AN APPROACH TO THE ARCHITECTONICAL METHOD THROUGH THE ANALYSIS OF THE DUTCH EMBASSY IN BERLIN BY KOOLHAAS & OMA - Besa, Eneko (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This article ventures into the investigation about method in architecture, that is, about the way in which we think and create architecture. In order to achieve such an objective, the article simply re-thinks a specific architecture that already exists, the Dutch Embassy in Berlin. In this way, architectonical object and work are considered the susceptible elements that provide the material knowledge that unravels the manner and the methodology by which they were conceived. A sensitive and intuitive itinerary through the graphic documents published about the embassy allows us to access a continuous narrative dissertation that deconstructs the conceptual issues that have constituted the building. Thus, this paper developed an object-based method, as opposed to traditional and orthodox text-based research. This does not preclude the inclusion of innumerable references related to the conceptual issues that we can find in this architectonical analysis (Ungers, Vidler, Somol, etc., see citations and bibliography). In this way, the paper differentiates itself from the scientific-historical research. Having it as a support, the paper opens a new way for future research which can be specifically focused on the architectonical project’s methodology. At times, this research development can be disconcerting. This is because architectonical method, our way of thinking and creating, is never analytically structured. Neither can a text that tries to unravel the creative method be strictly linear. For this reason, this text is an essay that tries to introduce us to the deepest motivations of a project, most of the time intertwined in the form of spiral paths, cyclical paths that unite and contradict each other at the same time. Therein lies the uniqueness of this study. A second article 1 complements this analysis of the Embassy with an itinerary that, in this case, extends its route to other buildings by Koolhaas. This second paper also uses other comparisons with other historical references, for example, Venturi. Both articles find in Koolhaas’ method strategies based on a paradoxical conceptual identity, a diagrammatic coherence that coexists with the greatest semantic inconsistency. The impossible concordance between form, meaning and image. The scepticism towards the impossible unity, which, at the same time, pursues a challenging unitary iconic condensation.